PENGARUH EDUKASI TERHADAP MINAT BERINVESTASI PASAR MODAL SYARIAH BAGI KAUM MILENIAL DI ERA REVOLUSI INDUSTRI 4.0 - Afriandi Jualiansyah; Dwi Sekar Utami; Noor Khumaidah; Ibnu Muttaqin (OIKONOMIKA: Jurnal Kajian Ekonomi dan Keuangan Syariah, 2022)
The research was conducted with the aim of testing the influence of education on the interest in investing in Islamic capital markets for millennials in the era of the industrial revolution 4 0. The method used in this research is a descriptive quantitative method with direct entry into the field (field research). The population in this study was millennials or gen z. The sample in this study was taken randomly with a total of 96 respondents. The data analysis technique used is a simple linear regression test in the form of a t-test using the SPSS 21 program. The method of data collection is done by spreading questionnaires or questionnaires through Google Forms. The results of this study show that education significantly affects the interest in investing in Islamic capital markets for millennials in the era of the industrial revolution 4.0.